Association Between 5-Star Nursing Home Report Card Ratings and Potentially Preventable Hospitalizations - Kira L. Ryskina MD, MS; R. Tamara Konetzka PhD; Rachel M. Werner MD, PhD (SAGE Publishing, 2018)
Nursing homes' publicly reported star ratings increased substantially since Centers for Medicare & Medicaid Services's Nursing Home Compare adopted a 5-star rating system. Our objective was to test whether the improvements in nursing home 5-star ratings were correlated with reductions in rates of hospitalization. We hypothesized that increased attention to 5-star star ratings motivated nursing homes to make changes that improved their star ratings but did not affect their hospitalization rate, resulting in a weakened association between ratings and hospitalizations. We used 2007-2010 Medicare hospital claims and nursing home clinical assessment data to compare the correlation between nursing home 5-star ratings and hospitalization rates before versus after 5-star ratings were publicly released. The correlation between the rate of hospitalization and a nursing home's 5-star rating weakened slightly after the ratings became publicly available. This decrease in correlation was concentrated among patients receiving post-acute care, who experienced relatively more hospitalizations from best-rated nursing homes. The improvements in nursing home star ratings after the release of Medicare's 5-star rating system were not accompanied by improvements in a broader measure of outcomes for post-acute care patients. Although this dissociation may be due to better matching of sicker patients to higher-quality nursing homes or superficial improvements by nursing homes to increase their ratings without substantial investments in quality improvement, the 5-star ratings nonetheless became less meaningful as an indicator of nursing home quality for post-acute care patients.